Performance evaluation of small independent hotels through management accounting indicators and ratios - Casqueira, Nuno (2021)
In order to succeed in a competitive tourism world, several management accounting techniques have been used by hoterliers. Management accounting techniques are connected with the decision-making process. Prior studies related to the characterization of management accounting in the lodging industry in several countries have recognised the ratio and indicators analysis as one of the management accounting techniques. Hotel chains use performance ratios and indicators, because thier management is accordingly with global rules. As in many other European countries, the Portugueses corporate structure directed to the independent hotel managers was conducted to obtain data, and has been submitted to a statistical analysis. In order to characterize the ratios and indicators it was used descritpive statistics. The conclusion shows that despite the importance of some of the operational ratios and indicators they are not being used, which allows some expectations relating to the proposal of a "tableau de bord" adapted to small independent hotels management.